2020
DOI: 10.1002/cam4.2920
|View full text |Cite
|
Sign up to set email alerts
|

Investigating association of perineural invasion on prostate biopsy with Gleason score upgrading at prostatectomy: A multi‐institutional analysis

Abstract: BackgroundThe significance of perineural invasion (PNI) in prostate cancer (PC) is unclear. A recent report of patients with pT2N0R0 PC found that PNI at prostatectomy was independently associated with higher Gleason score and more diffuse prostatic disease. We aimed to test our hypothesis that PNI on prostate biopsy in pT2N0R0 patients is associated with increased Gleason score upgrading at prostatectomy.MethodsWe identified 2892 patients status post prostatectomy with pT2N0R0 PC from three institutions, diag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(10 citation statements)
references
References 23 publications
2
8
0
Order By: Relevance
“…We identified pericytes cell type signature (Pericytes ENCODE 3 xcell p = 0.5E-04)and mesenchymal stem cell signature (MSC HPCA 3 xcell, p = 2.4E-04). Identified neuronal signature (Neurons ENCODE 2 xcell, p = 8.0E-07) in the metastatic IFN-γ-depleted subtype indicates presence of perineural invasion 60 , an indicator of aggressive prostate cancer 61,62 .…”
Section: Resultsmentioning
confidence: 99%
“…We identified pericytes cell type signature (Pericytes ENCODE 3 xcell p = 0.5E-04)and mesenchymal stem cell signature (MSC HPCA 3 xcell, p = 2.4E-04). Identified neuronal signature (Neurons ENCODE 2 xcell, p = 8.0E-07) in the metastatic IFN-γ-depleted subtype indicates presence of perineural invasion 60 , an indicator of aggressive prostate cancer 61,62 .…”
Section: Resultsmentioning
confidence: 99%
“…However, several recent studies about PNI on biopsy suggested that biopsy PNI seems less likely to predict GS upgrading. 28 Therefore, the association between biopsy PNI and Gleason grade upgrading warrant further investigation. For patients with biopsy PNI who are selected for AS, a repeat biopsy might be necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies that have evaluated the clinical significance of biopsy-detected PNI have yielded conflicting results. While some were unable to demonstrate an association with upgrading at prostatectomy 11 or BCR, 9 others found that PNI was associated with AP at RP 9,10 and BCR. 10 We found that patients with biopsy identified PNI were at increased risk of extraprostatic extension at RP compared to patients with no PNI, which is not surprising as PNI is a proven mechanism of PCa extracapsular spread.…”
Section: Discussionmentioning
confidence: 99%